Karawitan: source readings in Javanese gamelan and vocal music. - Becker, Judith, 1932-; Feinstein, Alan H. (Michigan papers on South and Southeast Asia, 1988)
Volume 3, Appendix 1: Glossary and index of technical terms mentioned in the texts. Appendix 2: Javanese cipher notation (titilaras kepatihan) of musical pieces mentioned in the texts. Appendix 3: Bibliographies of authors. Bibliography of sources mentioned by authors, translators, editors, and consultants.